Nurse Anesthetists' Experience In Maintaining Patient Safety In The Operating Room With High Workload: A Phenomenological Qualitative Study - Lukas Handoko; Agustinus Purna Irawan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to explore in depth the experiences of nurse anesthetists in maintaining patient safety in operating rooms with high workloads. A qualitative descriptive approach with a phenomenological approach was used to explore the subjective meaning of nurse anesthetists towards their work challenges. Data were collected through in-depth interviews with ten nurse anesthetists in a general hospital with a minimum work experience criterion of two years. The results of the study identified five main themes, namely: (1) high workload characterized by high volume of operations and limited rest time, (2) the impact of workload on physical and psychological conditions and patient safety, (3) adaptation strategies such as time management, spiritual approaches, and team communication, (4) preparedness in dealing with emergency situations, and (5) the need for institutional support from hospital management. Senior nurses tend to rely more on experience, spirituality, and emotional control, while junior nurses need more supervision and advanced training. The conclusion of this study shows that high workload significantly affects the work performance and well-being of anesthesia nurses. Individual coping strategies and institutional support are key to maintaining patient safety and maintaining anesthesia nurse addiction in a high-intensity work environment. This study provides an important contribution to more humanistic hospital policies and supports frontline health workers.